If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying A + -1B + C + -1D + E + -1F = -6 Solving A + -1B + C + -1D + E + -1F = -6 Solving for variable 'A'. Move all terms containing A to the left, all other terms to the right. Add 'B' to each side of the equation. A + -1B + C + -1D + E + B + -1F = -6 + B Reorder the terms: A + -1B + B + C + -1D + E + -1F = -6 + B Combine like terms: -1B + B = 0 A + 0 + C + -1D + E + -1F = -6 + B A + C + -1D + E + -1F = -6 + B Add '-1C' to each side of the equation. A + C + -1D + E + -1C + -1F = -6 + B + -1C Reorder the terms: A + C + -1C + -1D + E + -1F = -6 + B + -1C Combine like terms: C + -1C = 0 A + 0 + -1D + E + -1F = -6 + B + -1C A + -1D + E + -1F = -6 + B + -1C Add 'D' to each side of the equation. A + -1D + E + D + -1F = -6 + B + -1C + D Reorder the terms: A + -1D + D + E + -1F = -6 + B + -1C + D Combine like terms: -1D + D = 0 A + 0 + E + -1F = -6 + B + -1C + D A + E + -1F = -6 + B + -1C + D Add '-1E' to each side of the equation. A + E + -1E + -1F = -6 + B + -1C + D + -1E Combine like terms: E + -1E = 0 A + 0 + -1F = -6 + B + -1C + D + -1E A + -1F = -6 + B + -1C + D + -1E Add 'F' to each side of the equation. A + -1F + F = -6 + B + -1C + D + -1E + F Combine like terms: -1F + F = 0 A + 0 = -6 + B + -1C + D + -1E + F A = -6 + B + -1C + D + -1E + F Simplifying A = -6 + B + -1C + D + -1E + F
| 2q+58=4q+50 | | 2s-35=131 | | 1.3h+3.7h=5 | | 50-7k=24 | | 0.8c+9=8(0.6c-2) | | 6(k+4)=3k-12 | | -2x=3x+3 | | 5z-96z+2z+4=12z-156 | | 4x+1=.15 | | 12b+3whenb=-4 | | 1/3=954/s | | 6c=3(c+4)-c | | 5z-96z+2z+4=2(6z-78) | | 1.8=0.03x-58.32 | | 4x+35x=21x+28 | | 2+4(x-7)=5-4(x-5) | | 8x+47=8(x+6) | | -1+3x=3+25x | | 5(3m-4)-8=-88 | | f(x)=x^3-28x+48 | | 6(2x+5)=2 | | x^2+3y^2-3z^2-3xy-2xz-2yz=-1997 | | -3(2g+1)+3g=6g+3 | | 6z-38=130 | | 5n^2+2n-14=-7 | | 9x-58=7x | | (8x-16)=180 | | 5n^2+2n-14n=-7 | | (1/2)(5n-6)=3n | | -s+10=9s+6 | | y-2xy+4x=1 | | 10=(1/3)(w-15) |